2018
DOI: 10.1038/s41598-018-22512-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of growth rate on graphene lattice-defect formation within a single crystalline domain

Abstract: Chemical vapor deposition (CVD) is promising for the large scale production of graphene and other two-dimensional materials. Optimization of the CVD process for enhancing their quality is a focus of ongoing effort and significant progress has been made in decreasing the defectiveness associated with grain boundaries and nucleation spots. However, little is known about the quality and origin of structural defects in the outgrowing lattice which are present even in single-crystalline material and represent the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 24 publications
0
25
1
Order By: Relevance
“…The comparatively higher number of growth domains and the rather high growth coverage is suggested to cause these structures to coalescence in more defective manner with higher amount of grain boundaries. Cao et al mentioned a similar issue as a source of defect formation during growth in their theoretical studies . Furthermore, potentially due to higher number of seed formations and resulting higher growth rate, it is observed that the surface coverage of FD grown samples is higher than that of HO grown samples with multilayer to bulk growth zones (Figure S3(a) and (b), Supporting Information).…”
Section: Adsorption Energy and Dissociation Energy Barrier Values Of mentioning
confidence: 99%
“…The comparatively higher number of growth domains and the rather high growth coverage is suggested to cause these structures to coalescence in more defective manner with higher amount of grain boundaries. Cao et al mentioned a similar issue as a source of defect formation during growth in their theoretical studies . Furthermore, potentially due to higher number of seed formations and resulting higher growth rate, it is observed that the surface coverage of FD grown samples is higher than that of HO grown samples with multilayer to bulk growth zones (Figure S3(a) and (b), Supporting Information).…”
Section: Adsorption Energy and Dissociation Energy Barrier Values Of mentioning
confidence: 99%
“…In contrast, the D-band was almost non-existent in the spectra of samples transferred using our Soxhlet method (see Supporting Information Figure S3). Defects in graphene originate either during the CVD growth 25 or transfer 1 processes, but it is noteworthy that both transfer processes were handled strictly identically prior to the PMMA-removal step, indicating that our novel transfer approach introduces fewer perturbations into the graphene film, leading to improved electronic and optical properties. Raman spectroscopy data are commonly used to evaluate the degree of doping and strain in graphene samples.…”
Section: Resultsmentioning
confidence: 99%
“…[50] The quality of graphene product from CVD can be controlled with the use of different precursors. [51][52][53][54] For instance, Lee et al [55] produced mesoporous graphene nano-balls (MGBs) in large scale using a precursor assisted CVD with polystyrene balls and reduced iron as carbon source and catalyst respectively. A uniform number of graphene layers was achieved in this method as the carbon source was functionalised with sulfonic acid and carboxylic acid that facilitated homogeneous dispersion of template in catalyst solution.…”
Section: Fabrication Of Graphene and Related 2d Nanomaterials 21 Chemical Vapor Deposition (Cvd)mentioning
confidence: 99%
“…The quality of graphene product from CVD can be controlled with the use of different precursors [51–54] . For instance, Lee et al [55] .…”
Section: Fabrication Of Graphene and Related 2d Nanomaterialsmentioning
confidence: 99%